An Analysis of School Principals' Leadership in Implementing Inclusive Education in Early Childhood Education Institutions - Aditya Fitria Maulana Hidayat; Diana Diana; Yuli Kurniawati Sugiyo Pranoto (Yayasan Keluarga Guru Mandiri, 2025)
Inclusive education is a national policy established by the Indonesian government to realize equal access to education for all citizens. However, its implementation in early childhood education still faces various challenges due to limitations at the educational unit level. In this case, school principals play a strategic role in shaping an inclusive school culture through visionary, collaborative, and adaptive leadership. This study aims to understand school principals' perspectives on inclusive education and analyze the SWOT factors (strengths, weaknesses, opportunities, and threats) in their leadership. A qualitative descriptive approach was used through in-depth interviews and document analysis with three school principals: TK Fun and Play, TK Labschool UNNES, and TK Talenta Semarang. The results indicate that TK Fun and Play has strengths in clarity of vision and collaboration but relies heavily on external institutions for support. TK Labschool UNNES excels in using data as a basis for decision-making but faces challenges in collaborating with the foundation. Meanwhile, TK Talenta stands out in academic integration, with the challenge of unrealistic parental expectations. This study provides empirical contributions to policy development, leadership training, and an education system that is more responsive to the diverse needs of children from an early age.